2013
DOI: 10.1292/jvms.12-0537
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Adipocytokine, Omentin, Inhibits Agonists-Induced Increases of Blood Pressure in Rats

Abstract: ABSTRACT. Omentin is a recently identified adipocytokine, and we previously demonstrated that omentin played anti-inflammatory roles in vascular endothelial and smooth muscle cells. We also demonstrated that omentin induced vasodilation in rat isolated blood vessels. However, effects of omentin on blood pressure (BP) Adipocytes can secrete a variety of cytokines, termed adipocytokine. Obesity with an accumulation of visceral fat is one of the main risk factors for cardiovascular diseases, including hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 17 publications
1
14
1
Order By: Relevance
“…41 Furthermore, omentin inhibited noradrenaline-induced increases in the mean BP in rats. 42 Although serum omentin-1 levels were not correlated significantly with the mean BP in the current study (Pearson's correlation, r ¼ 0.116, P ¼ 0.28; data not shown), we speculated that omentin-1 affects the RVR by altering systemic conditions and local ocular factors in the retinal circulation.…”
Section: Discussioncontrasting
confidence: 61%
“…41 Furthermore, omentin inhibited noradrenaline-induced increases in the mean BP in rats. 42 Although serum omentin-1 levels were not correlated significantly with the mean BP in the current study (Pearson's correlation, r ¼ 0.116, P ¼ 0.28; data not shown), we speculated that omentin-1 affects the RVR by altering systemic conditions and local ocular factors in the retinal circulation.…”
Section: Discussioncontrasting
confidence: 61%
“…In addition, our ex vivo study demonstrated that omentin stimulates NO production and induces vasodilation in rat aorta (23). Furthermore, our current report demonstrated that acute intravenous administration of omentin inhibits agonists-induced increases of blood pressure in rats (5). To further advance these findings, we for the first time demonstrate that omentin inhibits SMC migration and vascular structural remodeling in this study.…”
Section: Discussionsupporting
confidence: 59%
“…Yamawaki et al demonstrated that omentin directly induced vasodilation of rat isolated blood vessels through endothelium-derived NO [ 32 ]. Moreover, their in vivo study demonstrated that intravenously injected omentin acutely inhibited agonist-induced increases of blood pressure in rats [ 44 ]. Recently, the same author showed that chronic omentin treatment inhibited monocrotaline-induced pulmonary arterial hypertension in rats via inhibiting vascular structural remodeling and abnormal contractile reactivity [ 45 ].…”
Section: Discussionmentioning
confidence: 99%